Human biology. - Gareth Stevens Publishing (Milwaukee, WI Gareth Stevens, 2002)
Explains what the human body is made of, how it works, what new discoveries are being made, and more.
Updated ed. of: Alive, the human biology files. Bethesday, Md. : Discovery Enterprises, 2000. (Discovery Channel School science collections)
Keywords: Human biology -- Juvenile literature; Human biology; Body, Human